Development communication and food security through smart greenhouse technology in Wanaraja Village, Garut, Indonesia - Farisal, Umar; Sari, Dian Nurvita; Pratama, Muhammad Rezha Insan (Program Magister Ilmu Ekonomi Pascasarjana Universitas Jambi, 2026)
Digital agricultural modernization has been widely promoted as a strategy to strengthen food security in rural Indonesia. However, its social and communicative implications remain insufficiently understood. This study examines the Smart Greenhouse (SGH) Wanaraja project in Garut Regency, West Java, as a case of technological innovation that demonstrates symbolic success but limited social transformation. An exploratory qualitative case study design was employed, with data collected through in-depth interviews, field observations, and document analysis across three sites: Wanaraja, Cikajang, and Banyuresmi. The findings indicate that the governance structure involving government agencies, state-owned enterprises, and private actors has produced a closed model of agricultural digitalization that limits community empowerment. Development communication within the project operates through three interconnected modalities—coordinative, instrumental, and performative—which reinforce technocratic governance and tokenistic participation. Although the Petani Milenial (Millennial Farmer) narrative generates public visibility through media representation, local participation remains largely procedural and labor-based, with little influence over decision-making. This vertical communication structure constrains knowledge transfer and reinforces epistemic dependency. Nevertheless, informal initiatives undertaken by local actors demonstrate the potential for grassroots learning and community agency. The study concludes that technological innovation without participatory communication risks reducing sustainability to symbolic rhetoric rather than substantive social transformation. It therefore highlights the importance of dialogic, participatory, and co-creative communication strategies for achieving socially inclusive agricultural development.